The Effect Of Warm Chocolate Drinking On Reducing Menstrual Pain In Adolescent Girls At SMP Swasta Yapim Air Bersih - Oktafirnanda, Yuka; MILA SYARI; -, RIZAWATI; WINDA AGUSTINA; Marlina, Marlina (Jurnal Maternitas Kebidanan, 2025)
Menstrual pain is pain that is felt during menstruation and interferes with the sufferer's activities. Menstrual pain can be treated with non-pharmacological treatment. The prevalence of dysmenorrhea reached 64.25% consisting of primary dysmenorrhea 54.89% and secondary dysmenorrhea 9.36%. Based on data from WHO, the incidence of dysmenorrhea is 1,769,425 people (90%) of women who experience dysmenorrhea with 10-16% of them experiencing severe dysmenorrhea. This research was conducted with the aim of finding out the effect of hot chocolate drinks in reducing menstrual pain in young women at Yapin Air Bersih Private High School. This research uses a pre-test design and one-group pre-test method. The statistical population of this research is female teenagers in grades 8 to 9 at Yapim Air Bersih Private High School, namely 25 people with purposive sampling of 15 people. This data was analyzed using the Wilcoxon test. The results of the study showed that there was a difference in the average decrease in menstrual pain before and after drinking hot chocolate, namely from 2.60 to 1.67 with an average increase of 9.3. The Wilcoxon test results show the A-symp Sig (2-tailed) p-value of 0.000. Consuming dark chocolate can be recommended to relieve pain during menstruation.